Mapping crop water productivity in the Nile Basin through combined use of remote sensing and census data - Karimi, Poolad; David, S.; Bastiaanssen, Wim G.M. (2011)
Remote sensed imagery in combination with secondary agricultural statistic was used to map crop water productivity (WP) in the Nile River Basin. Land productivity and crop tandardized gross value production (SGVP) were calculated at administrative level using the agricultural census data. Actual evapotranspiration (Eta) generated from remote sensing was used to assess crops consumptive water use. WP was then calculated by dividing SGVP by Eta in the cropped areas. Results show land productivity has a huge variation across the basin. SGVP per hectare in the basin varies from 20 $/ha to 1833 $/ha. Likewise SGVP, water productivity in the basin is highly variable. It ranges from 0.01 $/m3 to 0.2 $/m3. Observed patterns in the water productivity indicate that WP differences in the Nile basin are highly related to crop yield, which varies in different regions and also in irrigated and rainfed systems. Similarly, overall low WP is because of low yields, chiefly rainfed agriculture. This indicates that there is scope for enhancing WP in the Nile Basin through expanding irrigated agriculture and generally increasing yield.